WASTEWATER TREATMENT EFFICIENCY CASE OF OXYLAG WASTEWATER TREATMENT PLANT, MHAYA (MOROCCO) - A., Bouhlal; A., Chahlaoui; J., Bouzid; M., Farhaoui (International Journal of Research -GRANTHAALAYAH, 2017)
The wastewater from the urban commune of Mhaya (Morocco) was rejected directly into Ben Kazza river without treatment. This situation caused a widespread, massive, varied and insidious pollution of the environment. A wastewater treatment plant (WWTP) has been constructed in 2010 in order to preserve the nature surrounding the center. Called Oxylag, the plant has a nominal capacity of 6000 Equivalent Inhabitants. It is based on intensive treatment and it is considered as pilot and unique in Morocco. The treatment is consisting on three basins ventilated by insufflation of artificial air and a basin of finishing. The present study aim is the assessment of the purification performance of this plant during 2012, through the analysis of the pollution parameters (COD, BOD5 and TSS), which is the subject of the Moroccan standards on the quality of domestic wastewater defined by the decree Number 1607-06 of 25 July 2006. The results show a high purification performance in terms of carbon pollution removal (93% for BOD5, 79% for COD and 64% for TSS).